Conversion of a Disulfide Bond into a Thioacetal Group during Echinomycin Biosynthesis1. (2nd December 2013) - Hotta, Kinya; Keegan, Ronan M.; Ranganathan, Soumya; Fang, Minyi; Bibby, Jaclyn; Winn, Martyn D.; Sato, Michio; Lian, Mingzhu; Watanabe, Kenji; Rigden, Daniel J.; Kim, Chu‐Young
Abstract Echinomycin is a nonribosomal depsipeptide natural product with a range of interesting bioactivities that make it an important target for drug discovery and development. It contains a thioacetal bridge, a unique chemical motif derived from the disulfide bond of its precursor antibiotic triostin A by the action of an S‐adenosyl‐L‐methionine‐dependent methyltransferase, Ecm18. The crystal structure of Ecm18 in complex with its reaction products S‐adenosyl‐L‐homocysteine and echinomycin was determined at 1.50 Å resolution. Phasing was achieved using a new molecular replacement package called AMPLE, which automatically derives search models from structure predictions based on ab initio protein modelling. Structural analysis indicates that a combination of proximity effects, medium effects, and catalysis by strain drives the unique transformation of the disulfide bond into the thioacetal linkage.